Rhithrogena sartorii, a new mayfly species (Ephemeroptera: Heptageniidae) from North Africa - Zrelli, Sonia; Sartori, Michel; Bejaoui, Mustapha; Boumaiza, Moncef (Zootaxa, 2011)
A new species, Rhithrogena sartorii Zrelli & Boumaiza, sp. nov. is described in subimaginal, egg and nymphal stages from material collected in Northern Tunisia. This species shows affinities with members of the insularis species group. Features distinguishing the new species from other North African species, as well as from Rhithrogena insularis (from Corsica) and Rhithrogena nuragica (from Sardinia) are discussed.